Inpatient and outpatient treatment by specialist infant nutrition centres in Argentina effectively reduced child malnourishment - Santiano, Flavia Eliana (2023)
Aim: We evaluated the impact of inpatient and outpatient treatment provided by an infant nutritionfoundation in Las Heras, Mendoza, Argentina, and identified the factors that influenced nutritionalrecovery.Methods: This 2010-2018 retrospective study was based on 300 children up to five years of age with primary malnutrition, who were treated by an inpatient recovery centre then an outpatient prevention centre. We analysed the children?s height, weight, psychomotor development and living conditions when they were admitted, discharged and had received one year of outpatient treatment. There were full data on 241 children and just admission and discharge data for 59.Results: The children?s mean age on admission and weight were 14.8 ± 12.4 months and 6.9 ± 2.3kg and they stayed in hospital for a mean of 59.5 ± 49.7 days. We observed a significant increase in the weightfor-age, height-for-age and weight-for-height z-scores when all three time points were compared (p <0.001). Psychomotor development improved considerably in all patients after treatment. The factors that negatively influenced nutritional recovery were higher age at admission, sub-optimal breastfeeding practices, low birth weight, longer hospital stays, younger maternal age and overcrowded housing.Conclusion: Combining inpatient recovery and outpatient preventive treatment was effective forundernourished children in Argentina.